A graphdiyne oxide composite membrane for active electrolyte enhanced supercapacitors with super long self-discharge time. Issue 7 (24th January 2022) - Liang, Na; Wu, Xueyan; Lv, Yan; Guo, Jixi; Zhang, Xiuli; Zhu, Yingfu; Liu, Huibiao; Jia, Dianzeng
Abstract : GDYO/PVA self-assembled composite membrane as a separator effectively inhibited the self-discharge of AEESCs. The ultra-long self-discharge time is 37 160 s, and the capacitance retention rate is 95.1% after 8000 cycles. Abstract : Active electrolyte enhanced supercapacitors (AEESCs) are considered as promising tools for enhancing power capacity due to their high specific capacitance and simple construction. However, there are many challenges, such as severe self-discharge (SDC) and rapid capacity decay. Herein, we develop a novel strategy to fabricate AEESCs with the suppression of rapid SDC, in which a self-assembled composite membrane of graphdiyne oxide/polyvinyl alcohol (GDYO/PVA) is used as a separator. The new AEESCs show a SDC time of 37160 s (1.0 V–0.3 V), which is 153 times higher than that of commercial separators, as well as an excellent capacitance retention of 95.1% after 8000 cycles. The outstanding electrochemical performance of the GDYO/PVA composite membrane can be attributed to the inherent nano-network structure, excellent proton conductivity, and high selectivity of GDYO. This new strategy of a self-assembled composite membrane based on GDYO will provide new opportunities for constructing AEESCs with super long self-discharge time and high performance.